THE ROLE OF NATIONAL IDEOLOGY IN THE DEVELOPMENT OF THE COUNTRY - Sherzod K. Alimov (Web of Journals Publishing, 2024)
The article discusses the fact that the national ideology of our country unites all layers of the population and calls them to action for the common good and a single goal.
Keywords: Country, national ideology, development, value, outlook and society.